Republic of Azerbaijan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
This Selected Issues paper on Azerbaijan highlights that rapid non-oil growth since the onset of the oil boom has contributed to substantial reduction in poverty and inequality. To keep growth inclusive, there is a need to accelerate economic diversification and make the nonhydrocarbon private sector a self-sustaining engine of growth. Policy priorities include strengthening governance and the business environment and improving human capital and productive infrastructure to enhance the productivity of private investment. Expanding the relatively well-targeted social safety net will ensure coverage of the vulnerable groups.